Implementation of the Program Keluarga Harapan in Ratahan District, Southeast Minahasa Regency of Indonesia - Komansilan, Rine; Langkai, Jeane Elisabeth; Lumingkewas, Lexi (Technium Social Sciences Journal, 2021)
This study aims to analyze the implementation of the Program Keluarga Harapan in the Ratahan sub-district, Southeast Minahasa Regency. The article uses a qualitative approach. Techniques to study data in research, observation, interviews, and documents. Data sources, namely, program recipient communities, field implementers, and technical implementers. The results showed that: a). This program has not been socialized according to the program's objectives to the community, which is the program's target, b). The commitment of the technical and field implementers has not been formed according to program objectives, c). The available funding sources for implementers are not sufficient to support program implementation, e). social conditions of the community have not been formed to support the program, f). There is no accurate data available on the target beneficiary group of the program. For that, it is suggested: a). There is accurate data on the target group receiving the program, b). The program is socialized to the community and target groups, c). Determined technical and field implementers who are committed to implementing the program based on objectives, d). Funds available for program implementation, e). The community and target groups are conditioned to be critical in supporting programs.